Penerapan Teknologi Augmented Reality untuk Pengenalan Komponen Jaringan dan Cara Kerja TCP/IP berbasis Android - Lena Magdalena; Kusnadi Kusnadi; Muhammad Kahfi (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
Augmented reality is a term for combining real-world environment with virtual worlds. Augmented reality is becoming very popular today because besides interesting, also can be displayed in realtime. In general, augmented reality adds a digital object in reality with reference to specific objects in the real world, for example by using a marker. Therefore, in this thesis aims to create an application that displays a 3D object that contains information about the network components and the workings of TCP / IP by making use of the concept of augmented reality marker technique. A marker is a reference object in the real world as a marker so that the information can be displayed. The marker is made to function to call the 3D objects appear on the screen smartphone that uses the technique of introduction of basic colors of red, green and blue. The method used consists of several stages of research, namely data collection, analysis and system design and system implementation. Data collection method used is literature. Methods of analysis and design of systems using the Unified Modeling Language (UML). The programming language used for software development are C # (C-Sharp) with Unity applications and software SketcUp to create 3D objects as well as Android SDK to convert the file into the form of android. This application is successfully created by displaying a 3D object that can make users excited to get to know the physical network components and requires only an internet connection to download the initial marker.